Investigation of phosphorylated and O-glycosylated proteins in gestational diabetes mellitus - Kaleem, Afshan; Anwar, Tehreem; Iftikhar, Aqsa; Abdullah, Roheena; Mehwish Iqtedar, Mehwish; Aftab, Mahwish (Penerbit Universiti Kebangsaan Malaysia, 2024)
Gestational Diabetes Mellitus (GDM) is a common but temporary type of diabetes that develops among 10-20% of all pregnant women. It is a major cause of several pre- and post-pregnancy diseases in both mother and offspring. The main causative is altered pregnancy hormones that lead to deficient glucose metabolism. Complications can be preeclampsia, caesarean sections and cardiovascular diseases. This study was designed to determine the phosphorylated and glycosylated proteins present in GDM and to investigate the role of their post-translational modifications (PTMs) in the pathogenesis of GDM. The study was performed on 30 blood samples from pregnant diabetic women (diseased), 30 pregnant non-diabetic women (control) and 30 women without pregnancy and gestational diabetes (normal). Protein extraction was done from blood plasma, and phosphorylated and glycosylated proteins were determined by EnzymeLinked Immuno-Sorbent Assay (ELISA) by use of specific antibodies. This study showed that proteins found in GDM are highly phosphorylated and O-glycosylated (p<0.01). Furthermore, a bioinformatic investigation was done, which showed that blood coagulation proteins such as the Fibrinogen alpha chain and lipid metabolism-regulating proteins apolipoprotein E, L1 and C-III showed a high potential for phosphorylation, which suggests that phosphorylation can be used as a therapeutic marker in GDM.